Corporate Governance towards Enterprise Risk Management Disclosure in Indonesia Sharia Banks - Budiyah, Feriani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
Risk management is a strategy that can be applied to evaluate risk. Risk management is influenced by entities and other management (Ratna et al., 2019). The Committee of Sponsoring Organizations of the Treadway Commission (COSO) defines Enterprise Risk Management as a process that can be influenced by company management that is implemented in every company strategy and is designed to provide sufficient assurance to achieve company goals. Disclosure of risk management involving corporate governance seen from various factors is very important to study. This is based on the experience of companies listed on the IDX. This research is a type of quantitative research with descriptive method. The research design is intended to explain the characteristics of risk management disclosure and assess corporate governance and risk management disclosure in financial sector companies. The object of research is Sharia banks listed on the Indonesia Stock Exchange for the period 2021-2023. The results showed that these variables did not fully affect the enterprise risk of Sharia banks. It can be added with other variables or additional samples to make the result more accurate.